Manifestasi Klinis dan Diagnosis COVID-19 Multisystem Inflammatory Syndrome pada Anak - Hernita Perliyani (Cermin Dunia Kedokteran, 2021)
Coronavirus Disease 2019 (COVID-19) merupakan penyakit yang disebabkan oleh SARS-CoV-2. Di penghujung tahun 2020 telah ada 79 juta kasus terkonfirmasi COVID-19 di dunia. Kasus anak dengan COVID-19 sedikit dilaporkan, gambaran klinisnya umumnya lebih ringan dibandingkan dewasa. Namun, beberapa laporan dari Eropa dan Amerika Utara menggambarkan kelompok anak-anak dan remaja masuk ke ruang perawatan intensif dengan kondisi sindrom inflamasi multisistem atau COVID-19 multisystem inflammatory syndrome (CMIS) yang mirip Penyakit Kawasaki dan sindrom syok toksik. Coronavirus Disease 2019 (COVID-19) is a disease caused by SARS-CoV-2. At the end of 2020 there have been 79 million confirmed COVID-19 cases in the world. Few COVID-19 cases in children were reported, generally withmilder manifestation than in adults. However, recently there have been several reports from Europe and North America describing groups of children and adolescents admitted to the intensive care with COVID-19 multisystem inflammatory syndrome (CMIS) with similar symptoms as Kawasaki disease and toxic shock syndrome.